2012
DOI: 10.1590/s1983-51752012000300014
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da radioterapia adjuvante no resultado cosmético da reconstrução mamária imediata com retalho TRAM

Abstract: Impact of adjuvant radiotherapy on the cosmetic outcome of immediate breast reconstruction performed using a transverse rectus abdominis myocutaneous flap Impact of adjuvant radiotherapy on the cosmetic outcome of immediate breast reconstruction performed using a transverse rectus abdominis myocutaneous flap Impacto da radioterapia adjuvante no resultado cosmético da reconstrução mamária imediata com retalho TRAM ABSTRACT Background: The outcome of adjuvant radiotherapy performed after breast reconstruction us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The most reported complaint was erythema of the breast, followed by hyperpigmentation, present in 73.2% and 64% of the patients treated with radiation, respectively, what is in contrast with another study that assessed the effects of post-operatory radiotherapy, in which hyperpigmentation and fibrosis were detected in 52% of the patients. 30 The study by Hu et al 29 also demonstrated hyperpigmentation on the breast of women treated with radiotherapy, as well as xerosis, complaints reported in 20.9% of the irradiated patients in this study. This is due to the fact that the skin, an organ that is continually renewed, is highly susceptible to radiation injury, leading to acute and late cutaneous changes, and therefore, radiotherapy is associated to a higher prevalence of those ( p = 0.011).…”
Section: Discussionsupporting
confidence: 71%
“…The most reported complaint was erythema of the breast, followed by hyperpigmentation, present in 73.2% and 64% of the patients treated with radiation, respectively, what is in contrast with another study that assessed the effects of post-operatory radiotherapy, in which hyperpigmentation and fibrosis were detected in 52% of the patients. 30 The study by Hu et al 29 also demonstrated hyperpigmentation on the breast of women treated with radiotherapy, as well as xerosis, complaints reported in 20.9% of the irradiated patients in this study. This is due to the fact that the skin, an organ that is continually renewed, is highly susceptible to radiation injury, leading to acute and late cutaneous changes, and therefore, radiotherapy is associated to a higher prevalence of those ( p = 0.011).…”
Section: Discussionsupporting
confidence: 71%